Comparison of thermal solar collector technologies and their applications - Alarcón Villamil, Alexander; Hortúa, Jairo Eduardo; López, Andrea (TECCIENCIA, 2013)
This paper presents the operation of different thermal solar collector technologies and their main characteristics. It starts by providing a brief description of the importance of using solar collectors as an alternative to reduce the environmental impact caused by the production of non-renewable sources like coal and oil. Subsequently, it focuses on each solar concentrator technology and finishes with a theoretical analysis hub application in different industrial processes.